A type of novel fluorescent magnetic carbon quantum dots for cells imaging and detection. Issue 12 (26th September 2015) - Su, Xi; Xu, Yi; Che, Yulan; Liao, Xin; Jiang, Yan
Abstract: A new type of multifunctional fluorescent magnetic carbon quantum dots SPIO@CQDs( n ) ([superparamagnetic iron oxide nanoparticles (SPIO), carbon quantum dots, (CQDs)]) with magnetic and fluorescence properties was designed and prepared through layer‐by‐layer self‐assembly method. The as‐synthesized SPIO@CQDs( n ) exhibited different emission colors including blue, green, and red when they were excited at different excitation wavelengths, and its fluorescent intensity increased as the increase of CQD layer ( n ). SPIO@CQDs( n ) with quite low toxicity could mark cytoplasm with fluorescence by means of nonimmune markers. The mixture sample of liver cells L02 and hepatoma carcinoma cells HepG2 was taken as an example, and HepG2 cells were successfully separated and detected effectively by SPIO@CQDs( n ), with a separation rate of 90.31%. Importantly, the designed and prepared SPIO@CQDs( n ) are certified to be wonderful biological imaging and magnetic separation regents. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3956–3964, 2015.